Kepemimpinan Non Muslim Perspektif Islam: Tinjauan Al-Quran dan Hadist - Minan, Ahmad Khoiron; Afifi, Nizar (Universitas Nurul Jadid, 2020)
Leadership in Islam becomes a very interesting discussion to be discussed anytime and anywhere. Especially some time ago in Indonesia there had been a furious conversation about non-Muslim leadership. Speaking of non-Muslim leadership, of course, the Ulama from classical to contemporary times have a lot of views and opinions. Starting from the scholars who are pro with non-Muslim leadership and not a few who reject the existence of leaders from non-Muslim groups. We will review this discussion based on the Koran and Hadith. For the verses of the Koran we will focus on the QS. Al-Maidah verse 51, because that verse has been viral for some time and has become a trending topic in Indonesia. The method used in this paper is to use qualitative methods and extract data through research libraries. The Classical Ulama tend to reject non-Muslim leadership on the basis of maintaining the Islamic faith. While contemporary scholars tend to accept non-Muslim leadership with the assumption that what happened then and now is different, especially the presence of human rights makes everyone have the same rights when they want to or are a leader while still paying attention to existing restrictions.Keywords: Leadership, Non-Moeslim, and Islam.